A Modified Suction-Assisted Technique of Transfer of Diced Cartilage Graft to Carrier Material and Outcome of Direct Injection of Unwrapped Diced Cartilage in Rhinoplasty. Issue 4 (June 2017) - Bashir, Muhammad Mustehsan; Sohail, Muhammad; Khan, Farid Ahmad; Jan, Sadia Nosheen; Ansari, Hamid Hussain; Nazir, Umer; Hidayat, Zohaib
Abstract : Objective: To describe a modified suction-assisted technique (MSAT) of transfer of diced cartilage (DC) graft to a carrier material and to determine the clinical outcome of direct injection of unwrapped diced cartilage (UDC) in rhinoplasty. Place and Duration of Study: Department of Plastic Surgery, KEMU, Mayo Hospital, Lahore from February 2011 to January 2015 Methods: Forty-seven patients of both genders with types 0 to 3 saddle nose deformity were included. Patients with types 4 and 5 saddle nose deformity, diabetes, hypertension, hepatic or renal disorders were excluded. Open tip rhinoplasty was performed in all patients. Eighth and/or ninth costal cartilage was harvested. Cartilage graft was diced into 1 to 2 mm pieces. The DC graft was transferred to carrier material (1-mL syringe) with MSAT. The UDC was then injected into nose and clinical outcome was determined. Results: Out of 47 patients included in the study 62% were females with mean (standard deviation [SD]) age 22 (4) years. Thirty-four (72%) procedures were primary rhinoplasties while 13 (28%) were secondary rhinoplasties. Mean (SD) carrier material filling time was 12±3 seconds. All operating surgeons involved in study were satisfied with modified suction technique and declared it better than the traditional manual technique of filling the carrier material. Most of the patients were satisfied with their postoperative nasal appearance and complications were minimal. One patient required revision of surgery due to dorsal contour irregularities and another due to partial cartilage absorption at 13 ± 2 months follow-up. Conclusion: Our MSAT of transfer of DC and injection of UDC is simple, easy to perform, reduces operative time and produces acceptable cosmetic outcome as regard patient's satisfaction. Abstract : Supplemental Digital Content is available in the text